Historical criminology and the explanatory power of the past - Lawrence, Paul (Criminology & criminal justice, 2019)
To what extent can the past ‘explain’ the present? This deceptively simple question lies at the heart of historical criminology (research which incorporates historical primary sources while addressing present-day debates and practices in the criminal justice field). This article seeks first to categorize the ways in which criminologists have used historical data thus far, arguing that they are most commonly deployed to ‘problematize’ the contemporary rather than to ‘explain’ it. The article then interrogates the reticence of criminologists to attribute explicative power in relation to the present to historical data. Finally, it proposes the adoption of long time-frame historical research methods, outlining three advantages which would accrue from this: the identification and analysis of historical continuities; a more nuanced, shared understanding of micro/macro change over time in relation to criminal justice; and a method for identifying and analysing instances of historical recurrence, particularly in perceptions and discourses around crime and justice.